Measurement of the Platelet Response to Laser- induced Microvascular Injury - McKenzie, F. N; Arfors, K.-E; Matheson, N. A (Thrombosis and Haemostasis, 1974)
A study has been made of the biochemical factors underlying the platelet response to laser-induced microvascular injury. A platelet aggregating substance is produced at sites of laser-induced injury which markedly stimulates platelet activity at a site of injury inflicted a short distance downstream. Distal sites of injury are not similarly influenced if the distance between the injuries is increased or if the proximal site no longer shows platelet-stimulating activity. The stimulating effect of an adjacent proximal injury on platelet activity at a distal site is inhibited by local intra-arterial infusion of adenosine. Measurements of arterial blood pressure and microvascular blood flow velocity during adenosine infusion showed that its inhibitory effect on platelet activity is largely independent of its vasodilator properties. The effect of infusion of different adenosine phosphates (AMP, ADP, ATP) was also studied. Very small amounts of ADP markedly stimulated platelet activity and the emboli formed were similar to those normally produced at sites of laser injury. At high concentration AMP inhibited while ATP stimulated platelet activity in vivo. The results emphasise the fundamental role of ADP as a mediator of the platelet response at sites of laser- induced microvascular injury.